Vitamin A status in acute exacerbations of cystic fibrosis - Duggan, C; Colin, AA; Agil, A; Higgins, L; Rifai, N (The American journal of clinical nutrition, 1996)
Vitamin A is an essential nutrient for epithelial cell maintenance and repair, and it is known that infectious stresses may depress plasma vitamin A concentrations. Patients with cystic fibrosis are at risk for vitamin A deficiency because of fat malabsorption as well as for the inflammatory stresses of pulmonary exacerbations of their underlying disease. We therefore hypothesized that acute pulmonary exacerbations of CF would depress plasma retinol concentrations, and that these concentrations would return to baseline values when clinical symptoms improved. We prospectively studied 35 CF patients (mean age: 24.2 y) consecutively admitted with pulmonary exacerbations. Plasma retinol, vitamin E, retinol binding protein (RBP), and C-reactive protein (CRP) concentrations were measured on hospital admission and discharge. Dietary intake was measured by using a semiquantitative food-frequency questionnaire. Regression analysis was used to identify significant clinical and laboratory correlates of retinol concentrations. On admission, mean (+/- SD) concentrations of plasma retinol were 1.14 +/- 0.5 mumol/L compared with 1.70 +/- 0.6 mumol/L on discharge (P = 0.0001). Of 35 subjects, 8 (22.9%) had plasma retinol concentrations considered to be in the deficient range (< 0.70 mumol/L). Concurrently, mean concentrations of plasma RBP increased during hospital admission (from 1.46 to 2.24 mumol/L, P = 0.003), and the mean CRP concentration declined (from 25.7 to 9.8 mg/L, P = 0.002). Significant positive correlations were found between plasma retinol concentrations at admission and age, weight, body mass index, triceps-skinfold-thickness percentile, midupper arm circumference percentile, plasma vitamin E, and RBP concentration, thus suggesting that better-nourished patients had more optimal vitamin A status. At admission, plasma retinol concentrations were negatively correlated with maximum body temperature and CRP concentrations, which indicated that the body’s acute-phase response was associated with the depression in retinol concentrations. We conclude that plasma retinol concentrations are depressed in acute pulmonary exacerbations of cystic fibrosis, and that concentrations considered to be in the deficient range are common. Vitamin A metabolism during acute inflammatory stress deserves further study.